Educational level and the use of mental health services, psychotropic medication and psychotherapy among adults with a history of physician diagnosed mental disorders - Halme Marie; Rautava Päivi; Sillanmäki Lauri; Sumanen Markku; Suominen Sakari; Vahtera Jussi; Virtanen Pekka; Salo Paula (SAGE PUBLICATIONS LTD, 2022)
Background: The prevalence of mental disorders is increased among people of low socioeconomic status or educational level, but it remains unclear whether their access to treatment matches their increased need.
Aims: Our objective was to examine whether educational level as an indicator of socioeconomic status is associated with use of mental health services, psychotropic medication and psychotherapy in Finland.
Method: Cross-sectional data from a follow-up survey of a longitudinal, population-based cohort study were used to form a sample of 3,053 men and women aged 24 to 68 with a current or previous physician diagnosed mental disorder. The prevalence of mental disorders, mental health service use and educational level were assessed with self-report questionnaire. Educational level was determined by the highest educational attainment and grouped into three levels: high, intermediate and low. The associations between educational level and mental health service -related outcomes were assessed with binary logistic regression. Covariates in the fully adjusted model were age, gender and number of somatic diseases.
Results: Compared to high educational level, low educational level was associated with higher odds of using antidepressants (OR 1.35, 95% CI [1.09, 1.66]), hypnotics (OR 1.33, 95% CI [1.07, 1.66]) and sedatives (OR 2.17, 95% CI [1.69, 2.78]), and lower odds of using mental health services (OR 0.80, 95% CI [0.65, 0.98]). No associations were found between educational level and use of psychotherapy.
Conclusions: The results do not suggest a general socioeconomic status related mismatch. A pharmacological emphasis was observed in the treatment of low educational background participants, whereas overall mental health service use was emphasized among high educational background participants.